Transfection by Electroporation of Cancer and Primary Cells Using Nanosecond and Microsecond Electric Fields - Eivina Radzevičiūtė; Veronika Malyško-Ptašinskė; Jurij Novickij; Vitalij Novickij; Irutė Girkontaitė (MDPI AG, 2022)
Gene transfer into primary immune cells as well as into cell lines is essential for scientific and therapeutical applications. One of the methods used for gene transfer is electroporation (EP). EP is a method where a pulsed electric field (PEF) causes a highly transient permeability of the targeted cell membrane. In this work, we present the electrotransfection of CHO-K1, 4T1 cell lines, and primary murine DCs with detectable protein-encoding plasmids in the sub-microsecond range. Microsecond (µs)- and nanosecond (ns)-range pulsed electric field transfection protocols were used. The efficiency of electrotransfection was evaluated using green fluorescent protein (GFP)-encoding plasmids (4.7 kbp; p-EGFP-N1) and plasmids expressing a firefly luciferase and red fluorescent protein (tdTomato) (8.5 kbp; pcDNA3.1(+)/Luc2 = tdT)). It was shown that the used nsPEFs protocol (7 kV/cm × 300 ns × 100, 1 MHz) ensured a better transfection efficiency than µsPEFs (1.2 kV/cm × 100 µs × 8, 1 Hz). Plasmid size and concentration had a strong impact on the cell transfection efficiency too. We also showed that there were no significant differences in transfection efficiency between immature and mature DCs. Finally, the nsPEF protocols were successfully applied for the stable transfection of the CHO-K1 cell line with the linearized pcDNA3.1(+)/Luc2 = tdT plasmid. The results of the study are applicable in gene therapy and DNA vaccination studies for the derivation of optimal electrotransfection conditions.